The Metallome as a Link Between the “Omes” in Autism Spectrum Disorders - Stanton, Janelle E.; Malijauskaite, Sigita; McGourty, Kieran; Grabrucker, Andreas M. (Frontiers in Molecular Neuroscience, 2021)
Metal dyshomeostasis plays a significant role in various neurological diseases such as Alzheimer’s disease, Parkinson’s disease, Autism Spectrum Disorders (ASD), and many more. Like studies investigating the proteome, transcriptome, epigenome, microbiome, etc., for years, metallomics studies have focused on data from their domain, i.e., trace metal composition, only. Still, few have considered the links between other ‘omes,’ which may together result in an individual’s specific pathologies. In particular, ASD have been reported to have multitudes of possible causal effects. Metallomics data focusing on metal deficiencies and dyshomeostasis can be linked to functions of metalloenzymes, metal transporters, and transcription factors, thus affecting the proteome and transcriptome. Furthermore, recent studies in ASD have emphasized the gut-brain axis, with alterations in the microbiome being linked to changes in the metabolome and inflammatory processes. However, the microbiome and other ‘omes’ are heavily influenced by the metallome. Thus, here, we will summarize the known implications of a changed metallome for other ‘omes’ in the body in the context of ‘omics’ studies in ASD. We will highlight possible connections and propose a model that may explain the so far independently reported pathologies in ASD.